2011
DOI: 10.1177/1471301211398988
|View full text |Cite
|
Sign up to set email alerts
|

The organisation of dementia care by families in Malta: The experiences of family caregivers

Abstract: This paper discusses the experiences of dementia family caregivers in Malta. The study design was essentially exploratory as this is the first funded social research on dementia in the island of Malta. In-depth semi-structured interviews were conducted in October 2008 with 17 caregivers. Identification of caregivers was through their relatives' attendance at a hospital based outpatient memory clinic. Interviews were recorded, transcribed and when required, phrases were translated from Maltese to English. A the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 50 publications
(92 reference statements)
0
32
0
Order By: Relevance
“…Instead, the female participants felt it was their responsibility to perform certain caring tasks that, they believed, were inappropriate for male family members to do. Similar to Ho et al (2003), the studies by Innes et al (2011) and Boughtwood et al (2011) were also dyadic in nature and it was not apparent if the gender expectation was identical across different cultures, particularly the Chinese culture, and, if so, how this applied to the intergenerational members of a family unit living together under one roof.  Lines 1-5 of para 1 in page 10: This cultural role expectation may permeate to the next generation of family caregivers as demonstrated in Boughtwood et al's study (2011) by the female grandchildren's willingness to assist older female family members in performing intimate caring tasks when compared to the males in the study sample.…”
Section: Reviewer:mentioning
confidence: 72%
See 1 more Smart Citation
“…Instead, the female participants felt it was their responsibility to perform certain caring tasks that, they believed, were inappropriate for male family members to do. Similar to Ho et al (2003), the studies by Innes et al (2011) and Boughtwood et al (2011) were also dyadic in nature and it was not apparent if the gender expectation was identical across different cultures, particularly the Chinese culture, and, if so, how this applied to the intergenerational members of a family unit living together under one roof.  Lines 1-5 of para 1 in page 10: This cultural role expectation may permeate to the next generation of family caregivers as demonstrated in Boughtwood et al's study (2011) by the female grandchildren's willingness to assist older female family members in performing intimate caring tasks when compared to the males in the study sample.…”
Section: Reviewer:mentioning
confidence: 72%
“…For smaller families, the live-in maid may be the only person staying with, and caring for, the person living with dementia in a one or two room high-rise apartment (Seow and Yap 2011;Tam et al 2018 In some non-Chinese cultures, caregiving provision for a person living with dementia is drawn along gender lines. For instance, in a Maltese study by Innes, Abela and Scerri (2011) involving husbands (n=2), wives (n=2), daughters (n=8), son (n=1), daughters-in-law (n=3), the findings revealed that daughters and daughters-in law were expected to provide physical care whilst the men took control of the decision-making. Developing this point further, a daughter caring for her mother in the study shared that she was told by her brothers of her obligation -as a daughter -to assume the caregiving role.…”
Section: Introductionmentioning
confidence: 99%
“…The rejection of formal care services further contributed to rotational care practices as these accommodated cultural expectations about children's obligation to provide care for their parents in a generation brought up in a society and historical time in which women are expected to be part of the labor force. Although similar care models have been described in Spain and Malta (Innes et al, 2011;Rivera et al, 2009), such care arrangements are extremely rare in Denmark, where formal care is generally more accepted and available.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of national dementia plans stress the need for a trained workforce, there is a dearth of cross‐national comparative studies in this area. Similar to other countries (Connolly et al ., ), dementia in Malta remains largely underdiagnosed (Caruana‐Pulpan & Scerri, ) and families report difficulties in supporting their relatives diagnosed with dementia (Innes et al ., ). In addition, although nursing students in Malta have adequate knowledge of dementia, they lack information on risk factors and caregiving issues (Scerri & Scerri, ).…”
Section: Introductionmentioning
confidence: 97%